Developmental coordination disorder questionnaire - translation and adaptation into Danish - Marta Topor; Anne Husted Henriksen; Rasmus Ahmt Rohde; Anna Bugge; Emma Bundgård Fals; Ida Jacobsen; Keenie Andersen; Jacob Wienecke (Taylor & Francis Group, 2024)
Background Developmental Coordination Disorder is a commonly occurring, but poorly recognised developmental condition characterised by difficulties with motor functions. Danish tests of children's motor functioning, which are currently available, are outdated and only applicable up to the age of seven years old. New tools are needed to enable easy and efficient screening of motor difficulties experienced by children living in Denmark.Aims/Objectives We translated and adapted the Developmental Coordination Disorder Questionnaire (DCDQ'07) into Danish and aimed to evaluate its utility.Materials and Methods A team of translators prepared the Danish version of the DCDQ'07 - DCDQ-DK. In total, 36 parents completed the questionnaire. The children completed fine and gross motor tests. Concurrent validity was tested using Pearson correlation on the DCDQ-DK and motor performance scores. Internal consistency was tested using Cronbach's alpha.Results The results show good concurrent validity (r = .311) and internal consistency (α = .80).Conclusions DCDQ-DK is well suited for use with Danish-speaking parents.Significance The tool will aid early assessment of motor difficulties in children of Danish-speaking parents. DCDQ-DK can be used by occupational therapists, educational and health professionals as well as researchers in national and international contexts.